THE EFFECT OF BABY MASSAGE ON BODY WEIGHT IN LBW BABIESAT PERMATA BUNDA PURWODADI HOSPITAL - Rosmala Kurnia Dewi; Anggita Septyani Permatasari; Pintam Ayu Yastirin (Jurnal Profesi Bidan Indonesia, 2023)
Background: BBLR cases are often associated with prematurity as the cause. There are many forms of intervention in handling BBLR babies, one of which is providing intervention aimed at optimizing the baby's growth and development, one of which is providing additional stimulation which includes touch and massage. Purpose: Analyze the differences in giving massage treatment to BBLR babies. Method: Quasi experimental research design, one-group pretest posttest design. The population in this study was BBLR at Permata Bunda Hospital. The total sample was 12 respondents using the total sampling technique. Results: The results of the research show that the p value is 0.000 < α 0.05, which indicates that Ho is rejected, which means significant weight gain before and after baby massage. Conclusion: The results of the baby massage treatment showed that there was a significant increase in body weight before and after the baby massage.